2005
DOI: 10.4049/jimmunol.175.12.7805
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Foxj1 Protects against Autoimmunity and Inhibits Thymocyte Egress

Abstract: Previous studies suggest that the forkhead transcription factor Foxj1 inhibits spontaneous autoimmunity in part by antagonizing NF-κB activation. To test this hypothesis, we ectopically expressed Foxj1 in the T cells of lupus-prone MRL/lpr mice by backcrossing a CD2-Foxj1 transgene against the MRL/lpr background. Strikingly, CD2-Foxj1-MRL/lpr animals showed a significant reduction in lymphadenopathy, pathogenic autoantibodies, and end-organ disease—but surprisingly, reversion of autoimmunity was not attributab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…In conclusion, together with previous observations showing that another forkhead transcription factor, FoxJ1, can regulate mouse T cell egress (44), our findings open a new unanticipated chapter in the biology of this large family of molecules to regulate T cell trafficking. Indeed, we have identified a new function of FOXO1 that regulates various immune response genes and is opposed by PI3K/Akt signaling in human T cells.…”
Section: Discussionsupporting
confidence: 79%
“…In conclusion, together with previous observations showing that another forkhead transcription factor, FoxJ1, can regulate mouse T cell egress (44), our findings open a new unanticipated chapter in the biology of this large family of molecules to regulate T cell trafficking. Indeed, we have identified a new function of FOXO1 that regulates various immune response genes and is opposed by PI3K/Akt signaling in human T cells.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have demonstrated that abnormal expression of Forkhead box J1 expression is upregulated and correlated with prognosis in patients with clear cell renal cell carcinoma FOXJ1 is associated with autoimmune diseases and certain inflammatory diseases (35,36). This association appears to be due to the ability of FOXJ1 to suppress T cell activity, resulting in spontaneous autoimmunity (37). In addition, FOXJ1 inhibits the humoral immune response in B cells, with FOXJ1 deficiency in B cells being associated with germinal center formation and the development of autoantibodies (38).…”
Section: Introductionmentioning
confidence: 99%
“…Interactions for Foxj1 with additional transcription-factor pathways in immunity almost certainly exist as suggested by the ability of Foxj1 to prevent egress of thymocytes in an apparently NF-κB-independent mechanism [13]. Furthermore, in respiratory systems, the sex-determining region on the Y chromosome (Sry)-related high-mobility group (HMG) box transcription-factor Sry-like HMG-box gene (Sox)17 can enhance Foxj1 promoter activity [14].…”
Section: Immunologically Relevant Foxes and Their Interactions With Infmentioning
confidence: 98%